2019
DOI: 10.1007/s00268-018-4839-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention with Somatuline© Delays the Progression of Pancreatic Neuroendocrine Neoplasms in a Mouse Model of Multiple Endocrine Neoplasia Type 1 (MEN1)

Abstract: Objective Long‐acting synthetic somatostatin analogues (SSA) are an essential part of the treatment of neuroendocrine neoplasms. We evaluated the chemopreventive effects of a long‐acting somatostatin analogue on the development of pancreatic neuroendocrine neoplasms (pNENs) in a genetically engineered MEN1 knockout mouse model. Materials and methods Heterozygote MEN1 knockout mice were injected every 28 days subcutaneously with the somatostatin analogue lanreotide (Somatuline Autogel©; Ipsen Pharma) or a place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Other interventions to prevent progression and development of metastases may be possible in the future and warrant study to pause progression of disease. Animal studies using lanreotide (Lopez et al 2019) and pasireotide (Quinn et al 2012, Walls et al 2016 After 6 years of follow-up, MRI revealed a liver lesion, while the pancreatic primaries remained unchanged. Subsequent 68 Gallium DOTATATE PET-CT scan showed liver and lymph node metastasis (A) as well as the small pancreatic primaries (B).…”
Section: Secondary Prevention Of Nf-pannets In Patients With Men1mentioning
confidence: 99%
“…Other interventions to prevent progression and development of metastases may be possible in the future and warrant study to pause progression of disease. Animal studies using lanreotide (Lopez et al 2019) and pasireotide (Quinn et al 2012, Walls et al 2016 After 6 years of follow-up, MRI revealed a liver lesion, while the pancreatic primaries remained unchanged. Subsequent 68 Gallium DOTATATE PET-CT scan showed liver and lymph node metastasis (A) as well as the small pancreatic primaries (B).…”
Section: Secondary Prevention Of Nf-pannets In Patients With Men1mentioning
confidence: 99%
“…Nevertheless, in a MEN1 -knockout (KO) mouse model, the somatostatin analogue lanreotide significantly delayed pNET progression. 7 In addition, a retrospective clinical study reported that long-acting repeatable octreotide appeared to retard pNET progression in a series of 40 MEN1-associated pNETs <2 cm, with an objective response rate of 10%. 8 Furthermore, in a prospective series of 42 patients from the same group, lanreotide autogel resulted in a significant increase in progression-free survival at a median follow-up of 73 months.…”
mentioning
confidence: 99%